Hubungan Kadar Kadmium Urine dengan Tekanan Darah pada Pasien Penyakit Jantung Koroner - Siti Syiehan Muhdalin; Cimi Ilmiawati; Hendriati Hendriati (Jurnal Ilmu Kesehatan Indonesia, 2021)
Background: One of the factors that affect Coronary Heart Disease and blood pressure is atherosclerosis. Atherosclerotic plaque formation is influenced by various risk factors. Recent research in various developed countries shows the role of cadmium in the formation of atherosclerotic plaques.Objective: To determine the relationship between urinary cadmium levels and blood pressure in coronary heart disease (CHD) patients at dr. M. Djamil Hospital Padang.Method: Samples were taken used random sampling with a sample size of 98 people. Patient data were obtained from the medical records of Dr. M. Djamil Hospital Padang, followed by direct data collection on the research subject.Result: Subjects had urinary cadmium values and blood presure within normal limits. Pearson correlation test showed no relationship between urinary cadmium and SBP (r=-0.05; p=0.626); DBP (r=-0.09; p=0.336) and MAP (r= -0.08; p=0.414). Based on multiple linear regression tests, cadmium was not a predictor of SBP, DBP, and MAP (adjusted R2=0.038; -0.002; 0.027; standardized β Coefficient= 0.035; 0.045; 0.043; p value= 0.760; 0.690; 0.708, respectively).Conclusion: in CHD patients that there is no relationship between urinary cadmium levels and blood pressure.